Improving Assertiveness in Preventing Sexual Harassment with Sumbang Duo Baleh Content Mastery in Elementary Education - Adha, Idyana; Syukur, Yarmis (Department of Guidance and Counseling, FIP, Undiksha, 2024)
Sexual harassment among elementary school students is a problem that requires special attention, especially in terms of increasing awareness and assertive behavior to prevent these events. This study aims to analyze the improvement of assertive behavior in preventing sexual harassment of elementary school students by using Sumbang Duo Baleh content mastery services. The research method used is quantitative research with an experimental approach. The design used in this research is quasi-experimental. The research sample amounted to 30 students selected by purposive sampling method, consisting of 15 experimental group students and 15 control group students with low learning discipline category. The data collection method used was a questionnaire with a questionnaire sheet instrument. The data analysis technique used is the Wilcoxon Signed Rank test and Kolmogorov-Smirnov 2 Independent Samples. The results showed that Sumbang duo Baleh content mastery services were effective in improving students' assertive behavior in preventing sexual harassment. This is indicated by a significant increase in the experimental group compared to the control group. This study concludes that sumbang duo baleh content mastery services can be applied to improve students' assertive behavior in preventing sexual harassment so that it can be an effective solution in education at the elementary school level.